The Horizon Europe AGEMERA Project: Innovative Non-Invasive Geophysical Methodologies for Mineral Exploration - J. Joutsenvaara; J. Joutsenvaara; M. Holma; M. Holma; P. Kuusiniemi; J. Korteniemi; H. Seivane; D. Marti-Linares; M. Schimmel; G. Casini; G. G. Buffett; M. Pirttijärvi; et al. (Advances in Geosciences)
The AGEMERA project (Agile Exploration and Geo-Modelling for European Critical Raw Materials) advances the exploration of critical raw materials in the EU by deploying innovative, non-invasive geophysical technologies. Funded by the Horizon Europe programme, it aligns with the European Critical Raw Materials Act to enhance resource security and sustainability. Utilising passive seismic methods, drone-based electromagnetic sensing, and muography, the project maps subsurface characteristics across multiple countries in Europe and Zambia. Outcomes are integrated into a dynamic web-based platform for enhanced co-visualisation of different data sets.